Public Sector Employment at Will: A Critical Analysis of Ethical Concerns and Recommendations for Public Administrators. (4th March 2018) - Goodman, Doug; Cohen, Galia
Abstract : Recent reforms have sought to increase accountability and flexibility in the public sector's personnel systems. One radical reform has witnessed a dismantling of civil service systems and replacing of them with employment at will (EAW) systems. Reforms of this kind have been more pronounced at the state and local government levels. Amid the reforms, scholars and public employees are skeptical of moving public employees to EAW systems, fearing the ethical status of EAW policies. This article moves beyond the basic question of whether the public sector should or should not adopt an EAW policy; instead, it focuses on analyzing primary ethical concerns associated with the implementation of EAW practices. Practical recommendations are presented to assist public at-will managers in meeting their ethical obligations toward their EAW employees.